Analysis of Learning Tools Based on Personal and Social Teaching Responsibility to Cultivate Responsibility - Nugroho, Agung Wahyu (Jurnal Evaluasi dan Pembelajaran, 2025)
This study aims to 1) analyze the feasibility of teaching tools based on the TPSR model in fostering student responsibility during PJOK learning in junior high school, 2) analyze the effectiveness of the TPSR model in fostering student responsibility during PJOK learning in junior high school. This study is a research and development using the steps of 4D, namely: define, design, development and disseminate. The research subjects were 8th grade students of junior high schools in Moyudan District. The trial conducted included two stages, namely a small-scale trial conducted on 32 students and a large-scale trial conducted on 64 students. The research instrument used observation guidelines. The data analysis technique used was quantitative data analysis in the form of the Aiken index, normality prerequisite test and paired sample t-test homogeneity test. The results of the study revealed that: (1) the product of the learning tool to foster personal and social responsibility of 8th grade students produced was feasible by meeting valid and practical criteria. The average V value = 0.95 with high criteria. (2) based on data analysis, the module product effectively fosters personal and social responsibility in junior high school students with the results of the paired sample t test obtaining a value of 0.000 which is less than 0.05, so there is a significant influence of the TPSR model soccer material learning device on personal and social responsibility. Based on the results of the research above, it can be concluded that the TPSR-based soccer game learning device in fostering the value of personal and social responsibility in junior high school students, and is feasible, practical, and effective for use in fostering the value of personal and social responsibility in junior high school students.